DESIGN OF “AKUSAHA” ANDROID-BASED APPLICATION IN THE FINANCIAL MANAGEMENT OF BATIK JETIS SIDOARJO SMEs COMMUNITY - Yanuar Nugroho; Fitri Retrialisca; Izmi Dwira Eriani (Jurnal Layanan Masyarakat, 2023)
As one of the commercial and industrial cities in East Java, Sidoarjo has great potential in developing the SMEs sector. Uncertain capital constraints are difficult for SMEs. The ability to manage the finances of SMEs entrepreneurs is very important for business performance and business continuity. Without an understanding of SMEs about basic economic concepts, SMEs are unable to make financial management decisions. Most SMEs entrepreneurs, including SMEs entrepreneurs in Sidoarjo, experience this problem in general. Of course the problems faced will have serious consequences in the future, such as capital problems and tax consequences which will certainly affect the sustainability of the SMEs business. This activity is carried out in the form of training and mentoring. This program introduces resource persons who are professionals in their respective fields, through lecture techniques, discussions and mentoring practices, to the application of knowledge sharing methods to create an operational management system for company accounting and financial management. These trainees are members of the Batik Jetis Sidoarjo association who need special treatment in order to quickly rise from adversity and increase their profits by studying operational management of corporate accounting, corporate financial management and corporate governance. The AKUsaha application is an Android-based application developed according to the needs of SMEs. After attending the training, the student team assists the SMEs financial management process using the AKUsaha application face-to-face with SME players every month on Saturdays and Sundays. As a result, SME actors can understand the flow of cash coming in and out of their business, so that they can provide consideration for making business economic decisions. In addition, it is also useful for SMEs for reporting annual tax returns to applying for business capital loans.